Finnegans Wake - Joyce, James; Henkes, Robbert-Jan Ed.; Bindervoet, Erik Ed.; Fordham, Finn Ed. (Oxford : Oxford University Press, 2012)
In Chapelizod, a suburb of Dublin, an innkeeper and his family are sleeping. Around them and their dreams there swirls a vortex of world history, of ambition and failure, desire and transgression, pride and shame, rivalry and conflict, gossip and mystery.
Keywords: Older Men; Dreams